Forest Cover Change in NamHa National Protected Area, Luangnamtha Province Between 2005-2015 - Phengvichith, Vansaleum (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study evaluates forest cover changes and their underlying causes in Nam Ha national protected area, Luang Namtha Province, between 2005 and 2015. Using data from Landsat 5 and Landsat 8 satellite images captured in 2005, 2010, and 2015, forest cover and land use types were analyzed and classified. The causes of these changes were further explored through stakeholder interviews and data collection at provincial and district levels, which were then compared with findings from satellite image interpretations. The results indicate a 3,230 (ha) increase in plantations forest area, accompanied by decreases in forest -2,061(ha), shrubland -359(ha), and non-forest areas -810(ha) from 2005 to 2010. Between 2010 and 2015, shrubland expanded by 2,751(ha), plantation forests grew by 1,133(ha), while forest cover declined by -3,441(ha), and non-forest areas decreased by -444(ha), relative to the total area of Nam Ha national protected area. The drivers of these changes include population growth, deforestation for agricultural expansion, and concessions for economic tree plantations, particularly rubber. This research provides critical insights for stakeholders, offering a foundation for forest management, educational initiatives, and policy development. It emphasizes the importance of sustainable strategies to enhance forest cover while balancing socio-economic needs, thereby contributing to regional development goals.